"Intertwangerlings": A Multiple (Auto) Ethnography of Journeys, Gentle Collisions-Hard Boundaries, Statues, and Tilt and Turn Gate/Bridges at the 13th International Congress of Qualitative Research. (February 2021) - Hodkinson, Alan; Houston, Ella; Denzin, Norman; Adams, Heather; Kirkpatrick, Davina; Kandemir, Asli; Maslen, Joseph; Mendus, Alys; Rhodes, Paul; Stronach, Ian
The article introduces the concept of the "intertwangle, " a concept grounded within the gentle collisions of delegates at the 13th International Congress for Qualitative Inquiry at the University of Illinois and the simultaneous retelling of multiple autoethnographies of such encounters. Through such encounters and "retellings, " perhaps a different way of thinking about autoethnography is developed. The article presents a story of a journey to and through the 13th Congress. A journey of no answers and no certainty—this journey is not a collaborative sharing of data but more of the gentle collisions and the recounting of different stories located within shared experiences. It is a simple journey bounded by way-markers of uncertainty, at times self-deprecation, loss, and death. It is a journey of new beginnings, of no ends—of uncertainty rather than certainty, revealing rather than obscuring and expanding rather than reducing.